Using flow cytometry to monitor glycoprotein IIb-IIIa activation. (3rd October 2018) - Frelinger, Andrew L.
Abstract: Platelet-to-platelet aggregation is critical to the formation of hemostatic thrombi which limit bleeding following vascular injury and also contributes to obstructive thrombi in acute myocardial infarction, stroke, or other thrombotic diseases. Platelet aggregation is mediated by platelet surface glycoprotein (GP) IIb-IIIa (integrin αIIbβ3, CD41/61) on adjacent platelets. Upon platelet activation by adenosine diphosphate (ADP), thrombin, or other platelet agonists, GPIIb-IIIa undergoes conformational changes from a "resting" bent conformation to an "activated" extended conformation. In GPIIb-IIIa's activated conformation, a binding site is exposed which interacts with the arginine-glycine-aspartic acid (RGD) residues in the fibrinogen alpha chain, permitting fibrinogen binding and cross-bridging of adjacent activated platelets. Consequently, changes in the state of GPIIb-IIIa activation closely correlate with fibrinogen binding and the degree of platelet-platelet aggregation. In contrast to radiolabeled ligand methods used for bulk receptor-binding studies, flow cytometry allows the rapid analysis of fibrinogen receptor expression on single cells, thereby enabling analysis of the kinetics of GPIIb-IIIa activation and differences between platelets in their expression of activated GPIIb-IIIa. The present review will consider the use of flow cytometry to monitor GPIIb-IIIa activation and its application in clinical and research settings.